The role and advantages of computer systems in agribusiness; Rolul si avantajele sistemelor informatice in agribusiness - Elena Cofas; Irina-Adriana Chiurciu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The agribusiness sector has continued to contribute significantly to Romania's GDP, and the positive results are due to Romania's agricultural potential, increased production, as well as investments in infrastructure and state-of-the-art tools made in recent years by large companies operating in this field. sector and thus contributed to increasing productivity. However, the agribusiness sector in Romania is far from reaching its maximum potential. Although Romania is a major exporter of agricultural products, the "produced in Romania" label is not enough to become a global player. Agribusiness companies should invest to understand the needs of customers and global markets and provide higher value-added products than other global players. Information systems as a broader, comprehensive form is an essential field of study in business administration and management - areas considered major in the economic area. Thus, IT systems must respond to issues related to the management of hardware, software, data, and computer networks, in a strategic way for business success. Today, IT systems are increasingly becoming a vital component of business success for an organization or an entrepreneur.
Keywords: M15; 330; agribusiness; computer system; market